Generation Z and Political Participation: Representation, Values, and Practices of Political Discourse through the Case of Maxwell Alejandro Frost - Rifqi Rifqi; Kambali Kambali (Lentera Demokrasi: Jurnal Ilmu Sosial, Politik, Hukum, Ekonomi dan Pemerintahan, 2026)
This article aims to analyze the dynamics of Generation Z’s political participation in the context of contemporary United States politics by highlighting the election of Maxwell Alejandro Frost as the youngest member of Congress and the first representative of Generation Z. This study employs a qualitative method with a literature review approach, analyzing media articles, survey reports, and statements from relevant figures. The findings indicate that Generation Z’s political engagement is characterized by identity awareness, concern for structural issues such as gun reform, climate change, healthcare, and reproductive rights, as well as demands for inclusive and civil political discourse practices. Furthermore, the study finds that openness to intergenerational dialogue, the relationship between faith and politics, and exemplary conduct in civil discourse are important factors in fostering sustainable political participation among Generation Z. This article contributes to enriching the study of youth politics by emphasizing the importance of dialogical and ethical approaches in modern democracy.